Pain in tropical spastic paraparesis/HTLV-I associated myelopathy patients Dor em pacientes com paraparesia espástica tropical/mielopatia associada ao HTLV-I - Carlos Maurício de Castro-Costa; Abelardo de Queiroz Campos Araújo; Carlos C. Câmara; Ayrton S. Ferreira; Terezinha de Jesus T. Santos; Samuel Bovy de Castro-Costa; Raimundo Neudson M. Alcântara; Graham P. Taylor (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: Tropical Spastic Paraparesis/HTLV-I Associated Myelopathy (TSP/HAM) is a chronic myelopathy, and pain has been mentioned as a frequent sensory symptom in this condition. The authors aimed at analyzing this symptom in a TSP/HAM patients series. METHOD: For this, 46 patients were analyzed considering demographic and clinical characteristics and complaint of pain as to verbal description, time of onset and classification, correlated with the degree of motor disability and type of pain. RESULTS: Among the 46 TSP/HAM patients, 28 (60.8%) complained of pain, predominant in the early phase of the disease. Most of the patients exhibited neuropathic characteristics of pain, correlated with increased motor disability. CONCLUSION: Pain in TSP/HAM patients is a frequent and early symptom, and the neuropathic type is predominant (57.1%) and paralleled with increased incapacitation. The pathogenic involvement of cytokines may possibly be involved in the meaning of this symptom in this condition. OBJETIVO: A Paraparesia Espástica Tropical/Mielopatia Associada ao HTLV-I (PET/MAH) é uma mielopatia crônica, e a dor tem sido mencionada como um sintoma sensitivo freqüente nessa condição. Os autores objetivam analisar esse sintoma numa série de pacientes com PET/MAH. MÉTODO: Para isso, 46 pacientes foram analisados considerando características demográficas e clínicas, e queixa de dor do ponto de vista da descrição verbal, tempo de início e classificação, correlacionados com o grau de incapacitação motora e o tipo de dor. RESULTADOS: Dentre os 46 pacientes com PET/MAH, 28 (60,8%) se queixavam de dor, predominando na fase inicial da doença. A maioria dos pacientes evidenciou características de dor neuropática, correlacionada com aumento da incapacitação motora. CONCLUSÃO: A dor em pacientes com PET/MAH é um sintoma freqüente e inicial, sendo o tipo neuropático predominante (57,1%) e em paralelo com maior incapacitação. O envolvimento patogênico das citocinas poderá possivelmente estar relacionado com o significado desse sintoma nessa condição clínica.